Application of Shape Analyses to Recording Structures of Marine Organisms for Stock Discrimination and Taxonomic Purposes - Lishchenko, Fedor; Jones, Jessica Briony (Frontiers in Marine Science, 2021)
Morphometric analysis of biogenic recording structures within marine organisms has applications in stock assessment, taxonomics, and ecomorphological studies, with shape variation markedly influenced by both genetics and the surrounding environment. Geometric morphometrics (GM) is an alternative approach to the ‘traditional’ method of collecting linear measurements and applying multivariate statistical methods to these data. Landmark- and outline-based GM methods are suggested to have several advantages over the ‘traditional’ method. Due to the increasing popularity of GM methods in the modern literature, this chapter first compares different morphometric techniques, and then reviews the methods applied to recording structures, with a focus on GM outline-based analyses. It is clear that outline methods have become a popular method of analysis for structures such as otoliths, particularly for the purpose of distinguishing between population components. However, for other structures such as beaks this technique is only in its early stages of application and is more difficult to apply, but shows great promise for future studies. The advantages of using a holistic approach, incorporating several techniques including outline analysis for stock identification purposes is discussed.